Should Credit Be Given for Autonomous Liberalization in Multilateral Trade Negotiations? - Mattoo, Aaditya; Olarreaga, Marcelo (World Bank, Washington, DC, 2014)
As each new round of multilateral trade negotiations approaches, there is a demand for a negotiating rule that would give credit for autonomous (unilateral) liberalization. The authors show that the feasibility, and desirability of such a rule depend on when it is instituted. A credit rule established at the beginning of a round of negotiations has a primarily distributional effect, favoring those who have already undertaken liberalization. Implementing such a rule would depend on the generosity of those who have not liberalized. The authors propose instead establishing a credit rule at the end of a round of negotiations, which creates an ex-ante assurance that any unilateral liberalization will receive credit in the next round. Such a rule would help induce, or enhance liberalization in some countries between negotiating rounds, by reducing the gains from retaining protection as negotiating currency. More strikingly, it could also lead to deeper levels of multilateral liberalization, and induce other countries to go further than they would in the absence of a rule. Most important, such an ex-ante rule would not rely on altruism to be generally acceptable.